Comparative study of thermal reaction norms for development in ants. Issue 2 (29th July 2014) - Kipyatkov, Vladilen E.; Lopatina, Elena B.
Abstract This is the first compilation of our research and data from the literature on the duration and thermal reaction norms for development in ants. Altogether, 97 regression lines characterizing the linear dependence of ant brood (egg, larval, prepupal and pupal) development on temperature were obtained for 33 species from 15 genera and three subfamilies. Significant positive correlations between the durations of different immature stages were revealed. We found differences between thermal reaction norms for development for various immature stages, some taxonomic groups, and southern and northern groups of species. All immature stages appeared to be shorter on average at 25°C in northern ants compared to southern species; this difference is insignificant only for eggs. Highly significant negative correlations were revealed between the temperature threshold for development (TTD) and the sum of degree‐days (SDD) for all immature stages. The latitudinal trends in intraspecific variation of thermal constants appeared to be opposite to those we observed at the interspecific level. At the latter, the coefficient of thermal sensitivity of development (i.e. the coefficient of linear regression of development rate on temperature) and TTD tends to decrease and SDD to increase from the south to the north. In contrast, at the intraspecific level, development became more temperature‐sensitive in northern populations, i.e. characterized by higher slopes of regression lines of development rate on temperature, and higher TTDs. The species of the genus Formica are characterized by the shortest and the most temperature‐sensitive immature development among all the ant species studied.